Comparing vegetative growth patterns of cultivated (Daucus carota L. subsp. sativus) and wild carrots (Daucus carota L. subsp. carota) to eliminate genetic contamination from weed to crop - Asharp, G.; Pieralli, S.; Sofkova-Bobcheva, S.; Ward, A.; McGill, S. (Elsevier, 2024)
Wild carrot is a problematic weed that can threaten the genetic purity of cultivated carrots by hybridization. Wild carrots must be controlled before flowering to avoid the undesirable crossing with cultivated carrots. Understanding wild carrot's vegetative growth pattern helps formulate sustainable weed management practices. However, little is known about the vegetative growth patterns of wild and cultivated carrots. A pot experiment was carried out to compare and model the vegetative growth pattern of different morphological traits in both wild and cultivated carrots. This study was executed in a glasshouse located in Palmerston North, New Zealand. A factorial randomized complete block design (RCBD) with two factors and four replications was used. The first factor was assigned to the carrot genotype (cultivated and wild) and the second factor to length of juvenile stages (12-weeks, 8-weeks, and 4-weeks). Plant height, leaf number, shoot fresh and dry weight, root fresh and dry weight, root diameter and root length were measured. Data were analyzed using analysis of variance (ANOVA), principal component analysis (PCA), correlation, and regression analysis. At the 8-week juvenile stage (9–11 leaves stage), wild carrot's shoot and root characteristics exhibited rapid growth. Correlation analysis indicated positive and significant (p < 0.05) correlations between above and below-ground morphological traits. PCA showed that morphological characteristics, except plant height, can be used to distinguish wild and cultivated carrots. To predict the vegetative growth pattern of most of the morphological traits of wild and cultivated carrots, power regression models were selected based on higher R2 and adj-R2 values and lower values of RMSE, AIC and BIC. The study showed wild carrots grew more quickly than cultivated carrots during the vegetative phase. It is recommended that appropriate weed management practices, such as hoeing, tilling, hand pulling, or herbicide spraying, be implemented before wild carrot leaf stages 9–11.
Keywords: Morphological trait; Carrot seed production; Vegetative growth; Weed management; Wild carrot